ANALISIS FAKTOR-FAKTOR YANG MEMPENGARUHI KINERJA PEGAWAI KANTOR REGIONAL (KANREG) I BADAN KEPEGAWAIAN NEGARA (BKN) PROPINSI DAERAH ISTIMEWA YOGYAKARTA (DIY) - Purnami , Erni Sri (2011)
This research took the title "ANALYSIS OF FACTORS AFFECTING THE PERFORMANCE OF EMPLOYEE IN REGIONAL OFFICE (KANREG) I BADAN KEPEGAWAIAN NEGARA (BKN) DAERAH ISTIMEWA YOGYAKARTA (DIY)". The mean purpose of this research is to test whether there are significant influences between leadership, organizational culture, and motivation to employee performance in Kantor Regional (Kanreg) I Badan Kepegawaian Negara (BKN) Propinsi Daerah Istimewa Yogyakarta (DIY). This research used primary data, which are in the form of questionnaires an 100 respondents. The methodused in this research is purposive sampling. The results of this research shows that leadership, organizational culture and motivation have significant influences to employee performance in Kanreg. I BKN DIY. The results obtained R2 data analysis for 0.479, it means that the variables of leadership, organizational culture, and motivation may explain the performance of employee for the remaining 47,9% and 52,1% influenced by other variables outside from this research.